(untitled) - Bettelheim, Frederick A. (Australia, 2004)
Over the years Bettelheim, Brown, and March's INTRODUCTION TO ORGANIC AND BIOCHEMISTRY has become the most respected and best-selling Organic and Biochemistry textbook on the market. Known for the successful way it meets the needs of students who take this course--from re-entry students to those heading directly into careers in the allied health fields--the book is acclaimed for the way it provides students a solid chemistry foundation that will serve them well long after they leave the course. In this edition, the authors continue the hallmarks that have made their book a classic in the field: a pedagogically rich learning framework; a wide variety of medical and biological applications; a visually dynamic art program, innovative "Chemical Connections" essays that focus on current issues in organic and biochemistry; and exceptionally strong and varied end-of-chapter problems. At the same time, they have extended their student focus by providing a greatly expanded interactive CD-ROM, as well as a new "Career Corner" portion on the Book Companion Web Site designed to help students make the connections between the chemistry they are learning today and their future careers. This text gives students a solid foundation of the chemistry of the human body, consistently demonstrating that a strong background in molecular structure and properties leads to better understanding of biochemical interactions. The strength of this book is its readability, its application to normal human biochemical pathways, as well as discussing biochemical conditions present in diseases.
Keywords: Chemistry, organic,Biochemistry